PUBLIC INTEREST IN COMPLEMENTARY NURSING THERAPY IN BONDOWOSO DISTRICT DURING THE COVID-19 PANDEMIC. - M.Elyas Arif Budiman (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Complementary therapy is the development of traditional therapies and some are integrated with modern therapies that affect individual harmony from psychological, psychological, and spiritual aspects. Complementary therapy can be in the form of health promotion, disease prevention or rehabilitation. Treatment using complementary therapies can improve health more thoroughly, especially in improving body health in the Covid-19 era. The design of this research is descriptive analytic with cross sectional approach. The population of this research is the Bondowoso community. The sample size of 149 respondents was recruited using simple random sampling technique. The instrument used in this study was a questionnaire about the interest in complementary nursing. The data used in this research is descriptive statistical analysis so that the results will be obtained in the form of frequency distribution. Data analysis aims at public interest in complementary nursing therapy in Bondowoso district during the Covid-19 pandemic. The results of the calculation of descriptive data on complementary treatment options that are often carried out by clients in Bondowoso Regency in the table above show that of the 88 respondents doing cupping therapy 38 (43.2%), acupressure treatment 36 (38.6%), acupuncture treatment 36 (14 , 8%), and herbal medicines 3 (3,4%). The conclusion of this study is in line with the results of the study, where the public's interest in complementary nursing is very high, it is a challenge for nurses, the search for nurses' abilities to practice nursing is also increasing, especially in the new habit era of COVID-19.